2009
DOI: 10.1074/jbc.m109.054973
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Phototoxicity of the Genetically Encoded Photosensitizer KillerRed

Abstract: KillerRed is the only known fluorescent protein that demonstrates notable phototoxicity, exceeding that of the other green and red fluorescent proteins by at least 1,000-fold. KillerRed could serve as an instrument to inactivate target proteins or to kill cell populations in photodynamic therapy. However, the nature of KillerRed phototoxicity has remained unclear, impeding the development of more phototoxic variants. Here we present the results of a high resolution crystallographic study of KillerRed in the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
171
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(180 citation statements)
references
References 56 publications
(61 reference statements)
9
171
0
Order By: Relevance
“…[9,10] The presence of a long water-filled channel that connects the chromophore with the external solvent, which facilitates the diffusion of molecular oxygen, is also crucial in the properties of KillerRed. [9,11] Another important ROS such as singlet oxygen ( 1 O 2 ) has also been detected from KillerRed, though to a lesser extent, [8] and it does not play a major role in the KillerRed CALI effect. [10] 1 O 2 , however, seems to be the main ROS that participates in CALI when using other FPs such as the enhanced (E)GFP.…”
Section: Introductionmentioning
confidence: 98%
“…[9,10] The presence of a long water-filled channel that connects the chromophore with the external solvent, which facilitates the diffusion of molecular oxygen, is also crucial in the properties of KillerRed. [9,11] Another important ROS such as singlet oxygen ( 1 O 2 ) has also been detected from KillerRed, though to a lesser extent, [8] and it does not play a major role in the KillerRed CALI effect. [10] 1 O 2 , however, seems to be the main ROS that participates in CALI when using other FPs such as the enhanced (E)GFP.…”
Section: Introductionmentioning
confidence: 98%
“…This approach has been of limited value because targeting proteins of interest mostly relied on microinjection of fluorophore-conjugated antibodies (Surrey et al, 1998;Jay and Sakurai, 1999). However, the development of Killer Red, a derivative of the Hydrazoa jellyfish chromoprotein anm2CP that generates at least 1000-fold increase in reactive oxygen species over green fluorescence protein (GFP), presents the possibility of simply expressing Killer Red fusion proteins (Bulina et al, 2006;Carpentier et al, 2009;Pletnev et al, 2009;Serebrovskaya et al, 2009;Destaing et al, 2010;Teh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have suggested that light-mediated KillerRed activation induces ROS generation (3,5) and apoptosis (5,7) and these data are consistent with our results. Analysis of KillerRed structure by an X-ray (19) and a high-resolution crystallographic study (20) revealed that a waterfilled channel that reacts with the chromophore is responsible for the generation of ROS, which is mainly composed of singlet oxygen (3,21). The intracellular localization of KillerRed that generates ROS is an especially critical factor for KillerRed-mediated cell cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%